5-fluorouracil in the treatment of scleroderma: a randomised, double blind, placebo controlled international collaborative study. Issue 11 (November 1990) - Casas, J A; Saway, P A; Villarreal, I; Nolte, C; Menajovsky, B L; Escudero, E E; Blackburn, W D; Alarcón, G S; Subauste, C P
Abstract : A six month controlled study of 5-fluorouracil in the treatment of scleroderma showed a modest benefit in skin scores, Raynaud's phenomenon, and patients' global assessment. Visceral organ and hand function were unaffected. Mild to moderate toxicity was common in the 5-fluorouracil treated patients but usually responded to dose reduction. Two patients receiving 5-fluorouracil died from causes seemingly unrelated to treatment. Significant clinical improvement in scleroderma was not noted in the first six months of treatment with 5-fluorouracil.